I Didn't Do Well in High School English - Fanselow, John F.; California Association of Teachers of English to Speakers of Other Languages ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Language study is classified through a series of definitions of important terms such as dialects, register, speech production, and function words. The content of communications is examined by attributing content to linguistic mediums. An example is presented to illustrate that teaching a language entails more than merely teaching grammar. The attribution of content to mediums other than linguistic ones is also discussed; for example, linguistic visual mediums are usually coded by their literal meanings. While it appears that determining content areas for instruction is simply a matter of relating student needs with teacher lessons, in fact a high level of interrelation exists between areas of language study. Language instruction requires attention to many different areas of language. A teacher can adapt teaching approaches such as the grammar translation method, the audiolingual approach, and situational language teaching by attributing the teacher's preferred area of content to the lessons. In this way a teacher can integrate all aspects of language instruction into the syllabus. (RW)
ERIC Note: In its: CATESOL Occasional Papers, Number 9, p.1-19, Fall 1983; Paper presented at the Annual CATESOL Conference (13th, Sacramento, CA, March 12, 1982).
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Course Content; English (Second Language); Grammar; Second Language Instruction; Teaching Methods; Opinion Papers; Speeches/Meeting Papers